2005
DOI: 10.1086/430803
|View full text |Cite
|
Sign up to set email alerts
|

A Multi-Instrument Study of the Helix Nebula Knots with theHubble Space Telescope

Abstract: We have conducted a combined observational and theoretical investigation of the ubiquitous knots in the Helix Nebula (NGC 7293). We have constructed a combined hydrodynamic + radiation model for the ionized portion of these knots and have accurately calculated a static model for their molecular regions. Imaging observations in optical emission lines were made with the Hubble Space Telescope's STIS, operating in a ''slitless'' mode, complemented by WFPC2 images in several of the same lines. The NICMOS camera wa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 44 publications
(67 reference statements)
4
32
1
Order By: Relevance
“…This is similar to the observed changes in clump frequencies in the Helix Nebula, which was recently discovered to be also a multiple-shell planetary nebula (MSPN) (Zhang et al 2012). The optical images of the Helix Nebula do not cover all radii (O'Dell et al 2005) and show a difference in number density at a line about 40% of the radius for the large knots. Matsuura et al (2009) described a low frequency of isolated H 2 clumps in the inner half of the nebula and a strong increase to a few hundred isolated knots per square arcminute in a region they called the inner ring (out to about 70% of the radius).…”
Section: Main Nebulasupporting
confidence: 85%
See 1 more Smart Citation
“…This is similar to the observed changes in clump frequencies in the Helix Nebula, which was recently discovered to be also a multiple-shell planetary nebula (MSPN) (Zhang et al 2012). The optical images of the Helix Nebula do not cover all radii (O'Dell et al 2005) and show a difference in number density at a line about 40% of the radius for the large knots. Matsuura et al (2009) described a low frequency of isolated H 2 clumps in the inner half of the nebula and a strong increase to a few hundred isolated knots per square arcminute in a region they called the inner ring (out to about 70% of the radius).…”
Section: Main Nebulasupporting
confidence: 85%
“…The required amount of ionizing UV photons can be obtained by a clumpy structure of the main nebula, allowing UV photons to escape. Such structures are established for some well-studied PNe such as the Helix Nebula (O'Dell et al 2005;Matsuura et al 2009) or the Ring Nebula (Speck et al 2003;O'Dell et al 2003). In Dalnodar & Kimeswenger (2011), the positions of the spokes of enhanced intensity in the shell of NGC 2438 was shown to be correlated to holes in the main nebula.…”
Section: Introductionmentioning
confidence: 83%
“…This value was calculated from the observed H 2 surface brightness in the Red Spider (Davis et al 2003), and employing the brightness-column density relationship of O'Dell et al (2005). The fractional abundances thus derived, relative to H 2 , are also listed in Table 2.…”
Section: Results and Analysismentioning
confidence: 99%
“…Its origin remains uncertain. Low-Js CO and H 2 observations of the Helix nebula show dense, neutral knots with ionized cometary tails located in the central region of the nebula (Huggins et al 2002;O'Dell et al 2005;Hora et al 2006;Matsuura et al 2007). Matsuura et al (2009) showed that it is in the inner region of the Helix, towards the central star, where tails are observed from the neutral globules probably created by the stellar winds from the central star (Meaburn & Boumis 2010;Matsuura et al 2009;Speck et al 2002).…”
Section: Introductionmentioning
confidence: 99%